A Perspective on the Trends and Challenges Facing Porphyrin-Based Anti-Microbial Materials - Jiang, Lu; Gan, Ching Ruey Raymond; Gao, Jian; Loh, Xian Jun (Small (Weinheim an der Bergstrasse, Germany), 2016)
The emergence of multidrug resistant bacterium threatens to unravel global healthcare systems, built up over centuries of medical research and development. Current antibiotics have little resistance against this onslaught as bacterium strains can quickly evolve effective defense mechanisms. Fortunately, alternative therapies exist and, at the forefront of research lays the photodynamic inhibition approach mediated by porphyrin based photosensitizers. This review will focus on the development of various porphyrins compounds and their incorporation as small molecules, into polymers, fibers and thin films as practical therapeutic agents, utilizing photodynamic therapy to inhibit a wide spectrum of bacterium. The use of photodynamic therapy of these porphyrin molecules are discussed and evaluated according to their electronic and bulk material effect on different bacterium strains. This review also provides an insight into the general direction and challenges facing porphyrins and derivatives as full‐fledged therapeutic agents and what needs to be further done in order to be bestowed their rightful and equal status in modern medicine, similar to the very first antibiotic; penicillin itself. It is hoped that, with this perspective, new paradigms and strategies in the application of porphyrins and derivatives will progressively flourish and lead to advances against disease. Photodynamic inhibition as a novel therapy utilizing different classes of photosensitizers (PSs) to resolve the issue of drug resistance of conventional antibiotics is reviewed. The development of diverse porphyrins and their incorporation as small molecules into polymers, fibers, and thin films is systematically summarized, and future challenges and general development directions are discussed.